2011
DOI: 10.2217/clp.11.41
|View full text |Cite
|
Sign up to set email alerts
|

Role of long-chain and very-long-chain polyunsaturated fatty acids in macular degenerations and dystrophies

Abstract: Macular degeneration is a progressive, bilateral eye disorder that damages the macula of the human eye. The most common form of macular degeneration is age-related macular degeneration (AMD), which is the leading cause of irreversible blindness in people older than 50 years in developed countries. Autosomal dominant Stargardt disease-3 (STGD3) is an inherited macular dystrophy that has clinical features similar to dry AMD, but occurs at a much earlier age. It is caused by a mutation in the elongation of very-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 104 publications
0
12
0
Order By: Relevance
“…The mechanism by which lipophenol may increase cell viability could be through enhancement of the cell integrity and/or the induction of cell proliferation. Indeed, beneficial effects of DHA as an antioxidant and protective agent have been already described [51,52] in RPE cells, in patients, and rats. Surprisingly, when substituted with ALA at position 3, an enhanced toxicity was observed with a CC 50 = 69.44 µM and an acute toxicity up to 80 µM.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which lipophenol may increase cell viability could be through enhancement of the cell integrity and/or the induction of cell proliferation. Indeed, beneficial effects of DHA as an antioxidant and protective agent have been already described [51,52] in RPE cells, in patients, and rats. Surprisingly, when substituted with ALA at position 3, an enhanced toxicity was observed with a CC 50 = 69.44 µM and an acute toxicity up to 80 µM.…”
Section: Discussionmentioning
confidence: 99%
“…Brain and retina tissues contain around 40% and 60% DHA of total PUFAs, respectively. DHA is present in high amounts in retinal photoreceptors and is therefore essential for visual function(Liu et al, 2011). Animal studies and human observational studies have suggested that there is an inverse relationship between dietary intake of n‐3 LCPUFAs and the risk of developing age‐related macular degeneration.…”
Section: Dha and Its Impact On The Structure And Function Of The Brainmentioning
confidence: 99%
“…Eyes with large drusen, severe macular atrophy, macular hemorrhage, or any grossly visible chorioretinal pathologic abnormalities were excluded. After the cornea, iris, ciliary body, and lens were removed, a 4 mm peripheral retina (PR) region in the nasal mid-PR was punched with a trephine because previous studies from our laboratory have already indicated that lipid profi les of PR do not differ substantially from lipid profi les of macular tissue ( 29,30 ). All punched human ocular tissues were stored in tubes fi lled with argon gas and kept at Ϫ 80°C.…”
Section: Lipid Extraction and Purifi Cation Of Lipids With Solid-phasmentioning
confidence: 99%